Chrysin ameliorates methotrexate-induced hippocampal neurogenesis impairment by suppressing of oxidative stress and upregulating antioxidant enzyme activity in rodents - Tanaporn Anosri; Soraya Kaewngam; Ram Prajit; Kornrawee Suwannakot; Nataya Sritawan; Anusara Aranarochana; Wanassanan Pannangrong; Jariya Umka Welbat; Peter Wigmore; Apiwat Sirichoat (PLoS ONE, 2026)
Methotrexate (MTX) is used in treating several malignancies. However, MTX neurotoxicity remains a significant clinical side effect, leading to cell division malformation, and neurogenesis impairment. Chrysin, a flavonoid compound found in natural products, demonstrates various biological characteristics, including neuroprotective and antioxidant properties. The purpose of this study was to investigate the ameliorative effect of chrysin on oxidative damage and neurogenesis impairment caused by MTX. Male Sprague-Dawley rats were randomly divided into four groups, including the vehicle, MTX (75 mg/kg), chrysin (10 mg/kg), and chrysin+MTX groups. Chrysin was orally administered for 15 days. MTX was administered intravenously on days 8 and 15. The hippocampal neural stem cells were evaluated using sex determining region Y-box 2 (sox2) and nestin immunofluorescence staining. Antioxidant enzyme expression and the levels of oxidative stress marker were assessed. Additionally, the expressions of nuclear factor erythroid 2-related factor 2 (Nrf2), brain-derived neurotrophic factor (BDNF), cAMP-response element binding (CREB), and phosphorylated CREB (pCREB) were evaluated using Western blotting. Results showed that MTX significantly decreased the activity of antioxidant enzymes and produced oxidative stress. MTX also impaired neurogenesis, evidenced by decreased sox2 and nestin-positive cells and decreased expression of Nrf2, BDNF, CREB, and pCREB in the hippocampus and prefrontal cortex. However, chrysin significantly reversed the effects of MTX on these parameters. In conclusion, chrysin exhibits neuroprotective effects against MTX-induced neurogenesis impairment by upregulating antioxidant enzyme activity, reducing oxidative stress, and improving protein expression related to neurogenesis.